EXPLORING STUDENTS’ TRANSLATION STRATEGY ON THE GLIMPSE OF US SONG BY JOJI - Muhammad Amril Fadli; Baharuddin; Lalu Ali Wardana (Journal of English Education Forum (JEEF), 2023)
Translating texts from one language to another is often used as a resolution to overcome many challenges nowadays, allowing individuals to understand content that they may not have been able to otherwise. In the case of song lyrics, translation can be particularly useful in helping individuals understand the meaning and emotion behind the words. This study explored the translation strategies employed by ten Translation and Interpretation (TI) students in translating the lyrics of Joji's Glimpse of Us song, and investigated their translation products whether they meet the criteria of good translation. Using a qualitative-descriptive research design, the study analyzed 23 sentences from the source text, finding that the most common strategy used was the use of a more general word (44%), followed by paraphrasing with unrelated words (21%) , by paraphrasing using related word (18%), by addition (9%), and omission (4%). The least common strategy was the use of loan words or loan words with explanations (3%). The study also evaluated the accuracy, naturalness, and clarity of the students' translation products based on Mona Baker's theory and the criteria of good translation proposed by Larson (1984) out of 230 total data collected, the study found 148 acceptable translations (64%) and 82 unacceptable translations (36%). These findings can inform future teaching practices in TI programs and contribute to the field of translation studies.